Topics in Time Delay Systems Analysis, Algorithms and Control - Loiseau, Jean Jacques.; Michiels, Wim.; Niculescu, Silviu-Iulian.; Sipahi, Rifat. (Lecture Notes in Control and Information Sciences,, 2009)
This book is primarily targeted to present the most recent trends in the field of control and dynamics of time delay systems. In this rapidly evolving field, the book successfully captures a careful selection of the most recent papers contributed by prominent active researchers in the field and collected under five parts: I analysis and methodology, II numerical methods and algorithms, III control and observation, IV propagation and flows, V delays effects in interconnected systems and networks. The themes of the chapters appropriately categorize the activities in the field as per the motivations discussed above.